(untitled) (Conferencea, 2024)
Sulkhan-Saba Orbeliani (1658-1725) was an outstanding Georgian figure of the Renaissance, an excellent poet, lexicographer, translator, diplomat and scientist. He gained great authority not only in his homeland, but also outside of it, as an illustration, we quote the words of the French missionary, Jean Richard: "He is considered the father of all of Georgia". We see Sulkhan-Saba Orbelian in the center of political and public life of the country together with King Vakhtang VI of Kartli. Sulkhan-Saba Orbeliani turns to the West for help and travels to Europe. The route of the trip was as follows: Constantinople, Marseille, Paris, Rome, other Italian cities. Finally, Constantinople and Georgia via Turkey. Sulkhan-Saba in Paris was close to Louis XIV. In Italy, Pope Clement XI.